TRADISI SYUKURAN BARAJAMA’ DALAM KEHIDUPAN MASYARAKAT DI KECAMATAN POLONGBANGKENG KABUPATEN TAKALAR - St. Maisyah Nur Ali; Elza Ramona2; Riswandi (2025)
Tradition is a set of beliefs, thoughts, attitudes, understandings, customs, methods, and individual practices that are carried out and passed down from generation to generation. The continuity of a community in carrying out cultural rituals is a cornerstone of a tradition's existence in the midst of community life. In Sulawesi, traditions have developed that are continuously maintained and preserved, such as the barajama' tradition, a form of thanksgiving tradition carried out by the people of Polongbangkeng Selatan District, Takalar Regency. This tradition is carried out as an expression of gratitude for the sustenance that has been given by Allah SWT. The purpose of this research is to discuss the implementation of the procession and the values contained within the tradition. Furthermore, this research also discusses the relevance of the barajama' thanksgiving tradition for the present day. Functional theory is used as an analytical framework to examine the relevance of the barajama' thanksgiving tradition for the people of South Polongbangkeng District today. This research is not only narrative-descriptive, but also analytical-descriptive. The method used in this research is the historical method, which consists of four stages: heuristics or source collection, verification or source criticism, interpretation, and historiography or historical writing. The research findings indicate that the barajama' tradition begins with congregational prayers at the home of the host, followed by a communal prayer, where the host gives alms to the congregation, and concludes with a communal meal. Furthermore, the barajama' tradition contains values that are integral to community life, including religious and social values. The relevance of the barajama' tradition today is less relevant when faced with developments in the era, particularly in the religious sphere.